The first Dutch SDHB founder deletion in paraganglioma - pheochromocytoma patients - Devilee Peter; Dullaart Robin PF; Jansen Jeroen C; Lenders Jacques W; Kunst Henricus P; van der Wielen Michiel; van Bunderen Patrick A; Grimbergen Anneliese EM; Bayley Jean-Pierre; Corssmit Eleonora P; Vriends Annette H; Losekoot Monique; et al. (BMC, 2009)
Abstract Background Germline mutations of the tumor suppressor genes SDHB, SDHC and SDHD play a major role in hereditary paraganglioma and pheochromocytoma. These three genes encode subunits of succinate dehydrogenase (SDH), the mitochondrial tricarboxylic acid cycle enzyme and complex II component of the electron transport chain. The majority of variants of the SDH genes are missense and nonsense mutations. To date few large deletions of the SDH genes have been described. Methods We carried out gene deletion scanning using MLPA in 126 patients negative for point mutations in the SDH genes. We then proceeded to the molecular characterization of deletions, mapping breakpoints in each patient and used haplotype analysis to determine whether the deletions are due to a mutation hotspot or if a common haplotype indicated a single founder mutation. Results A novel deletion of exon 3 of the SDHB gene was identified in nine apparently unrelated Dutch patients. An identical 7905 bp deletion, c.201-4429_287-933del, was found in all patients, resulting in a frameshift and a predicted truncated protein, p.Cys68HisfsX21. Haplotype analysis demonstrated a common haplotype at the SDHB locus. Index patients presented with pheochromocytoma, extra-adrenal PGL and HN-PGL. A lack of family history was seen in seven of the nine cases. Conclusion The identical exon 3 deletions and common haplotype in nine patients indicates that this mutation is the first Dutch SDHB founder mutation. The predominantly non-familial presentation of these patients strongly suggests reduced penetrance. In this small series HN-PGL occurs as frequently as pheochromocytoma and extra-adrenal PGL.